Against modal dualism - Franken, Dirk (European journal of philosophy, 2022)
Modal dualism is the claim that there is a space of epistemically possible worlds that exceeds the space of metaphysically possible worlds. In the present paper, I argue that modal dualism is false. I do so via an argument that differs from most previous arguments against modal dualism in that it does not rely on controversial semantic or epistemological assumptions like descriptivism, internalism or modal rationalism. The point of my argument is, instead, that modal dualism is internally inconsistent because it is the result of the failure to draw the proper conclusions from the abandonment of these semantic and epistemological assumptions. The relevant inconsistency manifests itself in the modal dualist notion of epistemic modality. For this notion to play the explanatory roles assigned to it by modal dualists, it has to be a notion of a genuinely epistemic kind of modality. But the only way to make sense of such a notion is via just those semantic or epistemological assumptions that the modal dualist is keen to avoid. Anyone willing to abandon these assumptions has to go further and detach the epistemic from the modal altogether.
First published: 16 August 2021
Gesehen am 28.03.2023